1976
DOI: 10.1111/j.1365-2621.1976.tb00721.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in quality of cassava roots during storage

Abstract: Changes that occurred during the storage of fresh cassava roots and their effect upon acceptability of the roots both for human consumption as a fresh vegetable and for animal feed purposes are reported. During storage there was a rapid accumulation of total sugars accompanied by a small decline in starch content. In those roots showing internal discolouration and deterioration the percentage of sucrose declined very dramatically. Although roots softened during storage they required a longer cooking time for h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

1978
1978
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 6 publications
1
11
1
Order By: Relevance
“…Similar findings have been reported by Shfali and Sudesh (2005) Cardenas, Gomez, & Hervas, 1976). The total titratable acidity of the flour increased significantly (p < .05) in both the packaging materials during storage; however, effects of packaging materials (P) as well as interaction of P × S were found to be nonsignificant (Table 3).…”
Section: Effect Of Packaging Materials and Storage Period On The Chsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar findings have been reported by Shfali and Sudesh (2005) Cardenas, Gomez, & Hervas, 1976). The total titratable acidity of the flour increased significantly (p < .05) in both the packaging materials during storage; however, effects of packaging materials (P) as well as interaction of P × S were found to be nonsignificant (Table 3).…”
Section: Effect Of Packaging Materials and Storage Period On The Chsupporting
confidence: 89%
“…From an initial value of 68.5%, the starch content decreased to 67% in HDPE packed sample and 66.2% in LDPE packed sample at the end of 180 days of storage. This decrease in the starch content may be ascribed to the conversion of starch into sugars which was evident by an increase in the total and reducing sugar content of WCF during storage (Booth, De Buckle, Cardenas, Gomez, & Hervas, ). The total titratable acidity of the flour increased significantly ( p < .05) in both the packaging materials during storage; however, effects of packaging materials ( P ) as well as interaction of P × S were found to be nonsignificant (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…While the starch content decreased, sugar content increased with both holding period of root and flour storage ( Table 3). The increase in sugar during storage was at the expense of the starch content of the root (Akingbala et al 1989;Booth et al 1974). Ihedioha et al (1996) and Akingbala et al (1989) reported that enzymatic hydrolysis of the starch could decrease the utilization quality of cassava roots.…”
Section: Effects Of Root Maturity and Root Storage On Proximate Compomentioning
confidence: 95%
“…According to Booth et al (1976) extended storage can have two adverse effects on quality as starches are converted to sugars and roots becoming fibrous thereby lengthening cooking time. To achieve a maximum period of storage for cassava roots, it must be made sure that they are not injured or squashed during harvesting, transport and storage as injuries accelerate the physiological deterioration of the tissue.…”
Section: Discussionmentioning
confidence: 99%